1992
DOI: 10.1002/jso.2930490309
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen, digital rectal examination, and transrectal ultrasound in predicting the probability of cancer

Abstract: Over a 4 1/2 year period, 1,940 asymptomatic men were entered in a prostate cancer detection program consisting of digital rectal examination (DRE), prostate-specific antigen (PSA), and transrectal prostate ultrasound (TRUS). Four hundred and sixteen biopsies were performed resulting in the diagnosis of 79 cancers; 82% had clinically organ confined tumors. A recommendation for biopsy was made in 260 (62%) based on the TRUS alone, 55 (13%) by DRE alone, 92 (22%) when the DRE and TRUS were both abnormal, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
(1 reference statement)
0
8
1
Order By: Relevance
“…Whereas initial studies in the mid 1980s suggested prostate ultrasound should be used as a primary tool to isolate prostate cancer [9], more recently it has been shown that it should be reserved for those men in whom the findings on DRE and/or PSA are not normal [7,8,10]. In our experience, DRE did not correlate with either the TRUS finding of a hypoechoic lesion or with the biopsy.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Whereas initial studies in the mid 1980s suggested prostate ultrasound should be used as a primary tool to isolate prostate cancer [9], more recently it has been shown that it should be reserved for those men in whom the findings on DRE and/or PSA are not normal [7,8,10]. In our experience, DRE did not correlate with either the TRUS finding of a hypoechoic lesion or with the biopsy.…”
Section: Discussioncontrasting
confidence: 68%
“…Numerous studies have been published on this diagnostic triad (PSA, DRE, and TRUS) to evaluate the effectiveness of this triad or on two of these methods that are related to prostate cancer [7,8]. The aim of this study was to present our experience with a new technique of real time 3-dimensional (3D) sonography-''4-dimensional (4D) TRUS'' guided prostate biopsy in the evaluation of patients with elevated levels of PSA.…”
mentioning
confidence: 98%
“…However, a proportion of the lesions that are palpable at DRE will be benign, and may be caused by conditions such as BPH, retention cysts, prostatic calculi, prostatic atrophy, fibrosis associated with prostatitis and non-specific granulomatous prostatitis. False positive rates for prostate cancer caused by DRE are as high as 40-50% 36,[65][66][67] and, although BPH nodules that originate in the peripheral zone rarely result in abnormal findings at DRE, it is more typical for BPH originating in the transition zone to be palpable and confused with cancer. 68 The incidence of these non-malignant masses increases with age, resulting in the fall of the positive predictive value of DRE (25% in men aged under 65 years compared with 12.5% in men over the age of 65 years).…”
Section: Characteristics Of Tumours Detected By Drementioning
confidence: 99%
“…25 Approximately 50-95% of localised prostatic tumours are palpable and could thus be detected by DRE. 32,36,[65][66][67][69][70][71][72][73] The evidence for a statistically significant difference between palpable and nonpalpable tumours is conflicting. Cooner and colleagues showed no difference in Gleason scores between palpable and impalpable lesions, 66 and Matthews and Fracchia found no difference between the two groups for the incidence of extracapsular disease spread in men with clinically localised prostate cancer.…”
Section: Characteristics Of Tumours Detected By Drementioning
confidence: 99%
See 1 more Smart Citation